Intraspecific variation and phylogeographic patterns of the grey-capped greenfinch Chloris sinica ssp. (Passeriformes: Fringillidae) - Joo-Eun Kim; Jong-Gil Park; Kyoung-Soon Jin; Chungoo Park; Dong-Ha Nam (Mitochondrial DNA. Part B. Resources, 2018)
To study the intraspecific variation of the grey-capped greenfinch Chloris sinica (Passeriformes: Fringillidae), we sequenced complete mitochondrial (mt) genome of the C. sinica ssp. prevalent in Ulleung Island, Republic of Korea. The full length of the genome is 16,812 bp, containing 37 genes (2 rRNAs, 13 proteins, and 22 tRNAs) with a putative control region (D-loop). A total of 98 single nucleotide polymorphisms (SNPs) in the full mt genome were retained for Ulleung Island population and these SNPs were greater than those of inland population compared to the reference China subspecies. The analysis of the SNPs revealed 18 SNPs for ND4 gene, with a dominant haplotype shared by Ulleung population compared to the reference China population. The phylogenetic analysis of the C. sinica subspecies showed that they are monophyletic, however, there is clear phylogenetic separation between China and Korea subspecies with strong support (100% bootstrap). These data will provide new insights into reconstruct the intraspecific phylogeographical patterns of C. sinica species.